High-temperature-resistant and high-salt-resistant polymer as well as preparation and application thereof

By using redox initiation system of phosphazene compounds and peroxides, copolymerizing acrylamide and 2-acrylamide-2-methylpropanesulfonic acid, the problem of hydrolysis and viscosity loss of oil repellent under high temperature and high salt conditions is solved, and the possibility of efficient crude oil recovery and industrial production is achieved.

CN119751751AActive Publication Date: 2025-04-04QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411969131.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing oil repellent is severely hydrolyzed under high temperature and high salt conditions, resulting in a decrease in viscosity loss and recovery rate. It is difficult for traditional initiators to achieve copolymer preparation with high AMPS content.

Method used

A redox initiation system composed of phosphazene compounds and peroxides was used to induce the copolymerization of acrylamide (AM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) to prepare a water-soluble polymer that is resistant to high temperature and high salt.

Benefits of technology

Under high temperature and high salt conditions, the prepared polymer has high viscosity and long-term thermal stability, which significantly improves crude oil recovery, and has mild reaction conditions, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751751A_ABST
    Figure CN119751751A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and high-salt-resistant polymer as well as preparation and application thereof, and belongs to the field of oilfield chemistry. The preparation method of the high-temperature-resistant and high-salt-resistant polymer comprises the following steps: initiating acrylamide (AM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) to be copolymerized by adopting a redox initiation system, so as to prepare the high-temperature-resistant and high-salt-resistant polymer, wherein the redox initiation system comprises a phosphazene compound as a reducing agent and peroxide as an oxidizing agent. The polymer disclosed by the invention has relatively high viscosity under high-temperature and high-salt conditions, and can be used as an oil displacement agent for a high-temperature and high-salt crude oil reservoir, so that the crude oil recovery rate is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oilfield chemistry, and specifically relates to a high-temperature and high-salt resistant polymer and a preparation and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] At present, the temperature of developing crude oil reservoirs is 50℃-85℃, and the mineralization is 5000-30000mg / L, which has a high crude oil recovery rate and has achieved significant economic benefits. With the continuous exploitation of crude oil, the reservoirs to be developed are facing the problems of higher temperature (85-120℃) and higher mineralization (30000-100000mg / L). The currently used oil displacement agents, especially polyacrylamide oil displacement agents, undergo violent hydrolysis under this high temperature condition, and then undergo strong complexation with calcium and magnesium ions under high mineralization, and even form precipitation. The extreme curling of the molecular chain under high salt conditions leads to serious viscosity loss, and the high viscoelasticity required as an oil displacement agent is lost. Secondly, the current oil displacement agent also has the problem of poor long-term thermal stability under high temperature conditions, which reduces the sweep coefficient of the oil displacement polymer, and thus greatly reduces the crude oil recovery rate. Therefore, the oil displacement effect on oil reservoirs under high temperature and high salt conditions is extremely limited. In order to improve the temperature resistance of polymers, a high content of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) is often introduced for copolymerization with acrylamide (AM). As disclosed in "Synthesis and Properties of Heat-Resistant and Salt-Resistant Acrylamide Copolymers", current initiators are suitable for copolymerization with low AMPS content and cannot be used for polymerization with a content of more than 40%, or the product after initiation of polymerization is difficult to obtain high viscosity under high temperature and high salt conditions, thus restricting the progress of chemical flooding technology.

[0004] Phosphazene compounds, also known as phosphazene bases, are organic compounds containing P=N. As alkaline catalysts, they are often used to catalyze the polymerization of cyclic ester monomers, cyclosiloxanes, isocyanates, epoxy compounds, acrylates, etc., and have achieved excellent results. These reactions require harsh anhydrous and oxygen-free polymerization conditions, so all monomers must be strictly dehydrated. The process is complicated and difficult to apply to the production of cost-sensitive oil-displacing polymers, which greatly limits the scope of use of phosphazene compounds. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a high temperature and high salt resistant polymer and its preparation and application, and a method and application of preparing a water-soluble high temperature and salt resistant polymer by initiating copolymerization of acrylamide (AM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) in aqueous solution using a phosphazene compound and a peroxide to form a redox system. The polymer of the present invention has a high viscosity under high temperature and high salt conditions, and can be used as an oil displacement agent for high temperature and high salt crude oil reservoirs, thereby further improving crude oil recovery.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing a high temperature and high salt resistant polymer, comprising the following steps:

[0008] A redox initiation system is used to initiate copolymerization of acrylamide (AM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) to prepare a high-temperature and high-salt resistant polymer; wherein the redox initiation system includes a phosphazene compound as a reducing agent and a peroxide as an oxidizing agent.

[0009] In a second aspect, a high temperature and high salt resistant polymer is obtained by the above preparation method.

[0010] The structural formula of the high temperature and high salt resistant polymer is as follows:

[0011]

[0012] Where x and y represent the degree of polymerization.

[0013] In a third aspect, the present invention provides the use of the above-mentioned high temperature and high salt resistant polymer in oil fields.

[0014] In a fourth aspect, an oil displacement agent for crude oil reservoirs comprises the above-mentioned high temperature and high salt resistant polymer.

[0015] One or some of the above technical solutions have the following advantages or beneficial effects:

[0016] (1) The present invention provides a redox initiation system composed of a phosphazene compound rich in nitrogen methyl and a peroxide. The P=N bond changes the electronic configuration of the nitrogen methyl, making it easier for the phosphazene molecule to generate free radicals. Multiple nitrogen methyl groups allow multiple free radicals to appear on one molecule, which can effectively increase the molecular weight of the polymer product, thereby ensuring high viscosity under high temperature conditions. At the same time, the volume of the polymer molecule is enlarged, and the polymer molecule is more difficult to curl under high salt conditions, ensuring the viscoelasticity of the polymer, thereby ensuring a higher crude oil recovery rate. The initiation system has mild reaction conditions, and simple deoxygenation in water can effectively initiate copolymerization of up to 80% of AMPS and AM. The polymer has high viscosity and long-term thermal stability under high temperature and high salt conditions. At the same time, the reaction conditions are extremely loose, which is completely suitable for current enterprise production and has prospects for industrial production.

[0017] (2) The redox initiation system based on phosphazene compounds and peroxides described in the present invention can obtain copolymers with an AMPS content of up to 80%. The polymerization system has simple synthesis conditions, low equipment requirements, is suitable for current production conditions, and is easy to industrialize.

[0018] (3) The redox initiation system based on phosphazene compounds and peroxides provided by the present invention achieves higher viscosity under low concentration and high mineralization conditions compared to traditional initiation systems (such as redox initiation systems composed of potassium persulfate and sodium bisulfite, and azobisisobutylamidine hydrochloride initiator).

[0019] (4) The copolymer prepared by initiation in the present invention has a high viscosity under high temperature and high salt conditions, and its high viscoelasticity can effectively improve the recovery rate of oil reservoirs. For Shengli Oilfield, if the recovery rate is increased by 8%, the reserves can be increased by more than 56 million tons, and the application prospects are broad. Therefore, the polymer products prepared by the redox initiation system formed by the phosphazene compound and peroxide described in the present invention can drive the industrial upgrading of the oilfield chemical industry, expand the scope of use of phosphazene compounds, reduce the harsh conditions required for the reaction, promote the conversion of new and old kinetic energy, increase crude oil production, and reduce mining costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 This is the infrared spectrum of the copolymer 11# sample prepared in Example 11 of the present invention;

[0022] Figure 2 This is the NMR spectrum of the copolymer 11# sample prepared in Example 11 of the present invention;

[0023] Figure 3 The relationship between the apparent viscosity and concentration of the copolymer 10# sample prepared in Example 10 of the present invention in a 58002 mg / L mineralized aqueous solution at room temperature;

[0024] Figure 4 The relationship between the apparent viscosity and temperature of the copolymer samples 10#, 11# and 12# prepared in Examples 10, 11 and 12 of the present invention in a 58002 mg / L mineralized aqueous solution;

[0025] Figure 5 The copolymer 11# prepared in Example 11 of the present invention was heated to 40°C and the shear rate was 6s -1 The viscosity of pure water solution with different concentrations;

[0026] Figure 6 The figure shows the effect of the AMPS ratio in the copolymer prepared in Comparative Example 1 of the present invention on the apparent viscosity of the product aqueous solution. DETAILED DESCRIPTION

[0027] In view of the problems in the prior art that it is difficult to obtain high viscosity under high temperature and high salt conditions, or that high-content AMPS polymerization cannot be achieved under high temperature resistance, the present invention proposes a preparation method for preparing a water-soluble temperature-resistant and salt-resistant polymer by using a phosphazene compound and a peroxide to form a redox system to initiate copolymerization of acrylamide (AM) and 2-acrylamide-2-methylpropane sulfonic acid (AMPS), so that the prepared polymer has a higher viscosity under high temperature and high salt conditions, and can be used as an oil displacement agent for Class III to Class V crude oil reservoirs, thereby further improving the crude oil recovery rate.

[0028] A typical embodiment of the present invention provides a method for preparing a high temperature and high salt resistant polymer, comprising the following steps:

[0029] A redox initiation system is used to initiate copolymerization of acrylamide (AM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) to prepare a high-temperature and high-salt resistant polymer; wherein the redox initiation system includes a phosphazene compound as a reducing agent and a peroxide as an oxidizing agent.

[0030] In some examples of this embodiment, the phosphazene compound is selected from One or more of;

[0031] Preferably, the phosphazene compound is When R1 is R2 and R3 are each independently -NH2, In addition to the groups of R2 and R3, R4 can also be any one of hydrogen, benzene ring, methyl, ethyl or -C6H4-4-OCH3, that is, R4 is selected from -NH2, Hydrogen, benzene ring, methyl, ethyl or -C6H4-4-OCH3.

[0032] Preferably, the phosphazene compound is When R is

[0033] Further preferably, the phosphazene compound is

[0034] In some examples of this embodiment, a co-solvent is also added. Preferably, the co-solvent is urea, sodium formate, isopropanol or sodium hypophosphite, and the added amount is 0 to 5% of the total mass of acrylamide (AM) and 2-acrylamide-2-methylpropane sulfonic acid (AMPS) monomers, preferably 0.2 to 1%.

[0035] In some examples of this embodiment, the amount of the redox initiator system added is 0.001 to 0.05% of the total mass of the acrylamide and 2-acrylamide-2-methylpropane sulfonic acid monomers.

[0036] In some examples of this implementation mode, the oxidant is a peroxide selected from hydrogen peroxide, sodium persulfate, potassium persulfate or ammonium persulfate, and the proportion of the oxidant is 30-70% of the redox initiation system.

[0037] In some examples of this embodiment, the mass ratio of the monomer acrylamide to the monomer 2-acrylamide-2-methylpropane sulfonic acid is (1-8):(1-8), preferably (2-6):(4-8), and more preferably (4-6):(4-6).

[0038] In some examples of this embodiment, the preparation method specifically includes:

[0039] (1) dissolving acrylamide monomer and 2-acrylamide-2-methylpropanesulfonic acid monomer in water to prepare an aqueous solution, and adjusting the pH;

[0040] (2) adding a reducing agent to the aqueous solution of (1), and then adding a co-solvent, and stirring evenly;

[0041] (3) Adjust the temperature of the aqueous solution to the reaction temperature, and evacuate to remove oxygen or protect with inert gas;

[0042] (4) adding an oxidant to the aqueous solution of (2) and stirring the mixture evenly, evacuating the mixture to remove oxygen or protecting the mixture with an inert gas, and reacting the mixture to obtain a polymer block;

[0043] (5) Cutting, granulating, drying and crushing the rubber block to obtain a granular polymer product P (AM / AMPS), that is, the high temperature and high salt resistant polymer.

[0044] In some examples of this implementation mode, in steps (1) and (2), the following steps may also be performed:

[0045] (1) dissolving acrylamide monomer and 2-acrylamide-2-methylpropanesulfonic acid monomer in water to prepare an aqueous solution, adding a co-solvent, and adjusting the pH;

[0046] (2) Add a reducing agent to the aqueous solution of (1) and stir evenly.

[0047] In some examples of this embodiment, in step (1), an alkaline solution is used to adjust the pH to 6-10, preferably 6-7.

[0048] The concentration of the aqueous solution is 10-40%, calculated based on the total mass percentage of the monomers of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0049] In some examples of this embodiment, in step (3), the reaction temperature is controlled at 10-60°C.

[0050] In some examples of this embodiment, in steps (3) and (4), the vacuum deoxygenation is performed by vacuum reaction at 25-45° C. for 6-10 hours.

[0051] In some examples of this embodiment, in steps (3) and (4), the inert gas is one or more of argon, nitrogen, and carbon dioxide.

[0052] In step (3), the inert gas protection is to move the mixture into an insulated incubator after the temperature drops to 10-15° C. and pass the inert gas for 15-60 minutes;

[0053] In step (4), the inert gas protection is continuous ventilation for 5-60 minutes, and the temperature is gradually reduced for 0.5-3 hours to obtain a polymer block.

[0054] As a preferred embodiment, steps (3) and (4) are protected by inert gas, which has a better apparent viscosity than the copolymer prepared under vacuum deoxygenation conditions.

[0055] Another typical embodiment of the present invention provides a high temperature and high salt resistant polymer obtained by the above preparation method.

[0056] The structural formula of the high temperature and high salt resistant polymer is as follows:

[0057]

[0058] Wherein x, y represent the degree of polymerization, and x, y are greater than 0.

[0059] The high temperature and high salt resistant polymer is subjected to a rotor shear rate of 7.34 s -1 When the sample concentration is 2000 mg / L and the mineralization is 58002 mg / L, the apparent viscosity is 19-50 mPa·s at 25°C, preferably 30-50 mPa·s, and the apparent viscosity is 9-25 mPa·s at 95°C, preferably 15-25 mPa·s.

[0060] A third typical embodiment of the present invention provides the use of the above-mentioned high temperature and high salt resistant polymer in oil fields.

[0061] A fourth typical embodiment of the present invention provides an oil displacement agent for crude oil reservoirs, comprising the above-mentioned high temperature and high salt resistant polymer.

[0062] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0063] Example 1

[0064] 20 g of acrylamide and 20 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160 mL of deionized water was added to prepare an aqueous solution, and sodium hydroxide was added to adjust the pH to 7. During the stirring process, 0.1 wt% of 5.86 mL of hexa(tetramethylguanidine)cyclotriphosphazene (HTGCP) aqueous solution and 0.2 g of urea were stirred evenly, and then 1.73 mL of 0.1 wt% ammonium persulfate aqueous solution was added, and then placed in a vacuum drying oven and reacted at 40°C for 8 hours to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 1#.

[0065] Example 2

[0066] 20 g of acrylamide and 20 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160 mL of deionized water was added to prepare an aqueous solution, and sodium hydroxide was added to adjust the pH to 7. During the stirring process, 0.1 wt% of 5.03 mL of PNX aqueous solution and 0.2 g of urea were stirred thoroughly, and then 2.96 mL of 0.1 wt% ammonium persulfate aqueous solution was added, and then placed in a vacuum drying oven and reacted at 40°C for 8 hours to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product - copolymer 2#.

[0067] Example 3

[0068] 20g of acrylamide and 20g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 6.01mL of 0.1 wt% HTGCP aqueous solution was added, 0.2g of urea was added, and after stirring evenly, 1.98mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven, and reacted at 25°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 3#.

[0069] Example 4

[0070] 20g of acrylamide and 20g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 5.06mL of 0.1 wt% PNX aqueous solution and 0.2g of urea were added. After stirring evenly, 2.93mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven and reacted at 40°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 4#.

[0071] Example 5

[0072] 20 g of acrylamide and 20 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160 mL of deionized water was added to prepare an aqueous solution, and sodium hydroxide was added to adjust the pH to 7. During the stirring process, 0.1 wt% of 4.71 mL of (NMe2)3P=NH aqueous solution and 0.2 g of urea were stirred evenly, and then 3.28 mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven and reacted at 40°C for 8 hours to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product - copolymer 5#.

[0073] Example 6

[0074] 20 g of acrylamide and 20 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160 mL of deionized water was added to prepare an aqueous solution, and sodium hydroxide was added to adjust the pH to 7. During the stirring process, 0.1 wt% of 3.16 mL of [(NMe2)3P=N)]3P=NH aqueous solution and 0.2 g of urea were stirred evenly, and then 1.84 mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven and reacted at 40°C for 8 hours to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product - copolymer 6#.

[0075] Example 7

[0076] 20g of acrylamide and 20g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 3.80mL of 0.1 wt% PNX aqueous solution and 0.2g of urea were added, and after stirring evenly, 2.20mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven, and reacted at 40°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 7#.

[0077] Example 8

[0078] 20g of acrylamide and 20g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 5.70mL of 0.1 wt% PNX aqueous solution and 0.2g of urea were added. After stirring evenly, 3.30mL of 0.1 wt% potassium persulfate aqueous solution was added, and then placed in a vacuum drying oven for vacuum reaction at 40°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 8#.

[0079] Example 9

[0080] 24g of acrylamide and 16g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 2.53mL of 0.1 wt% PNX aqueous solution and 0.2g of urea were added, and 1.47mL of 0.1 wt% potassium persulfate aqueous solution was added after stirring evenly, and then placed in a vacuum drying oven, and reacted at 40°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 9#.

[0081] Example 10

[0082] 20g of acrylamide and 20g of 2-acrylamide-2-methylpropanesulfonic acid were added to a reaction bottle, 160mL of deionized water was added to prepare an aqueous solution, and then sodium hydroxide was added to adjust the pH to 7. During the stirring process, 2.53mL of 0.1 wt% PNX aqueous solution was added, 0.2g of urea was added, and 1.46mL of 0.1 wt% potassium persulfate aqueous solution was added after stirring. Then, the mixture was placed in a vacuum drying oven and reacted at 40°C for 8h to obtain a polymer block. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 10#.

[0083] Embodiment 11

[0084] 90g of acrylamide and 90g of 2-acrylamide-2-methylpropanesulfonic acid were added to a beaker, 478mL of deionized water was added to prepare an aqueous solution, potassium hydroxide was added to adjust the pH to 7, 24.05mL of 0.1 wt% PNX aqueous solution and 0.9g of urea were added during stirring, and after the temperature dropped to 10°C, the mixture was transferred to an insulated thermos cup, 11.95mL of 0.1 wt% potassium persulfate aqueous solution was added after argon was passed for 20 minutes, and argon was passed for 10 minutes. The polymer block was obtained after the temperature was lowered for 1 hour from the highest temperature. The block was cut, granulated, dried and crushed to obtain a granular product-copolymer 11#.

[0085] Example 12

[0086] 72g of acrylamide and 108g of 2-acrylamide-2-methylpropanesulfonic acid were added to a beaker, 464mL of deionized water was added to prepare an aqueous solution, 0.9g of urea was added, and potassium hydroxide was added to adjust the pH to 7. During the stirring process, 29.31mL of 0.1% by weight PNX aqueous solution was added, and after the temperature dropped to 10°C, it was transferred to an insulated thermos cup, argon was passed for 20 minutes, and then 15.69mL of 0.1% by weight potassium persulfate aqueous solution of oxidant was added, and argon was continuously passed for 10 minutes. After the temperature was lowered from the highest temperature for 1 hour, a polymer block was obtained. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 12#.

[0087] Example 13

[0088] 90g of acrylamide and 90g of 2-acrylamide-2-methylpropanesulfonic acid were added to a beaker, 487mL of deionized water was added to prepare an aqueous solution, 0.9g of urea was added, and potassium hydroxide was added to adjust the pH to 7. During the stirring process, 17.59mL of 0.1% by weight PNX aqueous solution was added, and after the temperature dropped to 14°C, it was transferred to an insulated thermos cup, argon was passed for 20 minutes, and then 9.41mL of 0.1% by weight potassium persulfate aqueous solution of oxidant was added, and argon was continuously passed for 10 minutes. After the temperature was lowered from the highest temperature for 1 hour, a polymer block was obtained. The block was cut, granulated, dried, and crushed to obtain a granular product-copolymer 13#.

[0089] Embodiment 14

[0090] Under vacuum deoxygenation conditions, different from Example 10, the content of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) in the monomer was as high as 80%, and copolymer 14# was prepared.

[0091] Embodiment 15

[0092] Under the condition of inert gas protection, copolymer 15# was prepared, which was different from Example 11 in that the content of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) in the monomer was as high as 80%.

[0093] Comparative Example 1

[0094] The existing literature (Jin Zhiyuan, Shan Guorong, Pan Pengju. Preparation and temperature and salt resistance of AM / AMPS / SSS terpolymers [J]. Journal of Chemical Industry, 2023, 74(02): 916-923) discloses that the redox system used is traditional potassium persulfate and sodium bisulfite, and a series of samples with different AMPS contents (the mass ratios of AM to AMPS are 5:5, 6:4, 7:3, 8:2, and 9:1, respectively) are obtained at a polymerization temperature of 40°C with an initiator mass ratio of KPS:NaHSO3=4:1, an initiator concentration of 0.15wt%, a monomer concentration of 20wt%, a solution pH of 7, and a polymerization temperature of 40°C. The shear rate at 40°C in a pure water solution of 2000 mg / L is 6s -1 The viscosity under the conditions Figure 6 shown.

[0095] Obviously, under the same temperature and shear rate conditions, the viscosity of copolymer 11# prepared in Example 11 in pure water solutions of different concentrations is as follows: Figure 5 As shown. When the concentration of copolymer 11# is 800 mg / L, the viscosity has reached 206 mPa·s, which is higher than the viscosity of less than 150 mPa·s at 2000 mg / L in Comparative Example 1. When the concentration is 2000 mg / L, the viscosity reaches 477 mPa·s, which reflects the great advantages of the new initiator. In addition, the AMPS content in this embodiment is 50%, while the traditional redox system in Comparative Example 1 cannot obtain a sample with high viscosity at a high AMPS content.

[0096] Comparative Example 2

[0097] Existing literature (Yang H, Zhang J, Jiang H, et al. Study on the rheologicalproperties and salt resistance mechanism of an amphiphilic polymer with twin-tailed group[J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2024,700:134748. Page 4 of the text, Figure 5) disclosed: the P(AM-AMPS) copolymer obtained by copolymerizing AM with an AM content of 24.5% using azobisisobutylamidine hydrochloride (AIBA, V-50 initiator) has a concentration of 2200 mg / L and a mineralization degree of 98558 mg / L at 25°C, and the viscosity in the solution is close to 20 mPa·s.

[0098] The viscosity of copolymer 11# prepared in Example 11 of the present invention in a solution with a concentration of 2000 mg / L and a mineralization degree of 1160048 mg / L at 25°C is 33.3 mPa·s. Obviously, compared with Comparative Example 2, Example 11 shows higher viscosity under low concentration and high mineralization conditions.

[0099] Test Example 1

[0100] The high temperature and high salt resistant polymers obtained in the examples were respectively prepared into 2000 mg / L aqueous solutions, and the apparent viscosity of each aqueous solution was measured. The test results are shown in Table 1.

[0101] The test instrument is a Haake rheometer, the temperature is 25℃ and 95℃, and the rotor shear rate is 7.34s -1 The sample concentration is 2000mg / L, the mineralization is 58002mg / L, of which NaCl is 53360mg / L, CaCl2 is 1213mg / L, MgCl2 is 3429mg / L, and the calcium and magnesium ion concentration is 1542mg / L.

[0102] Table 1

[0103]

[0104]

[0105] It can be seen from the results in Table 1 that the high temperature and high salt resistant polymer provided by the present invention has a very high apparent viscosity under the conditions of 25°C and 95°C and a mineralization degree of 58002 mg / L, which can be obtained by Figure 4 It can be seen that the product exhibits excellent high temperature and high salt resistance. Among Examples 1-10, under the condition of vacuum deoxygenation, the copolymer 10# prepared in Example 10 has better apparent viscosity at 25°C and 95°C, and under the condition of inert gas protection, Examples 11-13 have better apparent viscosity than the vacuum deoxygenation condition, and the copolymer 11# prepared in Example 11 is the best.

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature and high salt resistant polymer, characterized in that: The following steps are involved: A redox initiation system is used to initiate copolymerization of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid to prepare a high-temperature and high-salt resistant polymer; wherein the redox initiation system comprises a phosphazene compound as a reducing agent and a peroxide as an oxidizing agent.

2. The preparation method according to claim 1, characterized in that: The phosphazene compound is selected from One or more of; The phosphazene compound is When R1 is R2 and R3 are each independently -NH2, R4 is -NH2, Hydrogen, benzene ring, methyl, ethyl or -C6H4-4-OCH3; the phosphazene compound is When R is Preferably, the phosphazene compound is 3. The preparation method according to claim 1, characterized in that: A co-solvent is also added, preferably, the co-solvent is urea, the co-solvent is urea, sodium formate, isopropanol or sodium hypophosphite, and the added amount is 0-5% of the total mass of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid monomers; Preferably, the amount of the redox initiator system added is 0.001 to 0.05 wt % of the total mass of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid monomers; Preferably, the oxidant is a peroxide selected from hydrogen peroxide, sodium persulfate, potassium persulfate or ammonium persulfate, and the proportion of the oxidant is 30-70% of the redox initiation system; Preferably, the mass ratio of the monomer acrylamide to the monomer 2-acrylamide-2-methylpropanesulfonic acid is (1-8):(1-8), preferably (2-6):(4-8).

4. The preparation method according to claim 1, characterized in that: The preparation method specifically comprises: (1) dissolving acrylamide monomer and 2-acrylamide-2-methylpropanesulfonic acid monomer in water to prepare an aqueous solution, and adjusting the pH; (2) adding a reducing agent to the aqueous solution of (1), and then adding a co-solvent, and stirring evenly; (3) Adjust the temperature of the aqueous solution to the reaction temperature, and evacuate to remove oxygen or protect with inert gas; (4) adding an oxidant to the aqueous solution of (2) and stirring the mixture evenly, evacuating the mixture to remove oxygen or protecting the mixture with an inert gas, and reacting the mixture to obtain a polymer block; (5) Cutting, granulating, drying and crushing the rubber block to obtain a granular polymer, that is, the high temperature and high salt resistant polymer.

5. The preparation method according to claim 1, characterized in that: The preparation method specifically includes: (1) dissolving acrylamide monomer and 2-acrylamide-2-methylpropanesulfonic acid monomer in water to prepare an aqueous solution, adding a co-solvent, and adjusting the pH; (2) adding a reducing agent to the aqueous solution of (1) and stirring evenly; (3) Adjust the temperature of the aqueous solution to the reaction temperature, and evacuate to remove oxygen or protect with inert gas; (4) adding an oxidant to the aqueous solution of (2) and stirring the mixture evenly, evacuating the mixture to remove oxygen or protecting the mixture with an inert gas, and reacting the mixture to obtain a polymer block; (5) Cutting, granulating, drying and crushing the rubber block to obtain a granular polymer, that is, the high temperature and high salt resistant polymer.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the pH is adjusted to 6-10 using an alkaline solution; Preferably, the concentration of the aqueous solution is 10 to 40%, calculated as the total mass percentage of the monomers of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid; Preferably, in step (3), the reaction temperature is controlled at 10 to 60°C; Preferably, in steps (3) and (4), the vacuum deoxygenation is carried out by vacuum reaction at 25-45° C. for 6-10 hours; Preferably, in steps (3) and (4), the inert gas is one or more of argon, nitrogen, and carbon dioxide; Preferably, in step (3), the inert gas protection is to move the mixture into an insulated incubator after the temperature drops to 10-15° C. and pass the inert gas for 15-60 minutes; Preferably, in step (4), the inert gas protection is continuous ventilation for 5-60 minutes, and the temperature is gradually reduced for 0.5-3 hours to obtain a polymer block.

7. A high temperature and high salt resistant polymer obtained by the preparation method according to any one of claims 1 to 6.

8. The high temperature and high salt resistant polymer according to claim 7 has the following structural formula: Where x and y represent the degree of polymerization; Preferably, the high temperature and high salt resistant polymer is subjected to a rotor shear rate of 7.34 s -1 When the sample concentration is 2000 mg / L and the mineralization is 58002 mg / L, the apparent viscosity is 19-50 mPa·s at 25°C and 9-25 mPa·s at 95°C.

9. Use of the high temperature and high salt resistant polymer according to claim 7 or 8 in oil fields.

10. An oil displacement agent for crude oil reservoirs, comprising the high temperature and high salt resistant polymer according to claim 7 or 8.

Citation Information

Patent Citations

  • Preparation method of ultrahigh molecular weight sulfonic acid-type polyacrylamide

    CN102453192A

  • Preparation method and application of temperature-resistant and salt-resistant six-arm star-shaped polyacrylamide

    CN113583177A

  • Catalytic processes for the controlled polymerization of free radically (Co)polymerizable monomers and functional polymeric systems prepared thereby

    US20040171779A1